2017
DOI: 10.1021/acs.inorgchem.6b02980
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchy of Supramolecular Arrangements and Building Blocks: Inverted Paradigm of Crystal Engineering in the Unprecedented Metal Coordination of Methylene Blue

Abstract: The aromatic methylene blue cation (MB) shows unprecedented ligand behavior in the X-ray structures of the trigonal-planar (TP) complexes MBMCl (M = Cu, Ag). The two isostructural compounds were exclusively synthesized by grinding together methylene blue chloride and MCl solids. Only in the case of AuCl did the technique lead to a different, yet isoformular, Au derivative with separated MB and AuCl counterions and no direct N-Au linkage. While the density functional theory (DFT) molecular modeling failed in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 38 publications
(45 reference statements)
3
37
0
Order By: Relevance
“…It is therefore confirmed that the experimental crystal structure is not the absolute minimum and that in the solid state the observed conformation is attributable to the crystalline packing forces. This phenomenon is similar to findings described in the literature 35,36 . The DFT optimized structure ( 4a ) is therefore deemed the appropriate conformer for further structural investigation in order to determine the potential 11β-HSD1 binding affinity of 4 .
Figure 8Atom-by-atom superimposition of the DFT optimized compound ( 4a , magenta) on the X-ray structure (blue) of the title compound (RMSD = 1.491 Å, performed using YASARA version 18.11.21 (YASARA Biosciences GmbH)).
…”
Section: Resultssupporting
confidence: 93%
“…It is therefore confirmed that the experimental crystal structure is not the absolute minimum and that in the solid state the observed conformation is attributable to the crystalline packing forces. This phenomenon is similar to findings described in the literature 35,36 . The DFT optimized structure ( 4a ) is therefore deemed the appropriate conformer for further structural investigation in order to determine the potential 11β-HSD1 binding affinity of 4 .
Figure 8Atom-by-atom superimposition of the DFT optimized compound ( 4a , magenta) on the X-ray structure (blue) of the title compound (RMSD = 1.491 Å, performed using YASARA version 18.11.21 (YASARA Biosciences GmbH)).
…”
Section: Resultssupporting
confidence: 93%
“…In this case, no major steric hindrance problem seems to be at work in the linear alignment of one P n lone pair with the Au( i ) vacant σ hybrid. The uncharged Au( i )Cl fragment can be, in principle, derived from a linear complex such as AuCl 2 – (ref. 31) or ClAuL upon the extraction of a Cl – anion or a L neutral ligand such as Me 2 S32 or R 3 P 33.…”
Section: Resultsmentioning
confidence: 99%
“…The latter, in turn, can be oxidized to restore the original MB + cation, and this feature makes it a valid redox agent in biochemistry where it plays relevant roles in the study of enzyme-catalysed redox reactions. Recently, despite the cationic nature of MB + , we found that its peculiar electronic ISSN 2056-9890 situation enables ligand behaviour towards MCl 2 fragments (M = Cu and Ag) through the central aromatic nitrogen atom (Canossa et al, 2017), thus proving that some properties of this common and widespread molecule are still to be discovered.…”
Section: Chemical Contextmentioning
confidence: 99%